Cardioprotection conferred by exercise training is blunted by blockade of the opioid system - Galvão, Tatiana F. G (2011)
OBJECTIVES: To investigate the effect of opioid receptor blockade on the myocardial protection conferred by chronic exercise and to compare exercise training with different strategies of myocardial protection (opioid infusion and brief periods of ischemia-reperfusion) preceding irreversible left anterior descending coronary ligation. INTRODUCTION: The acute cardioprotective effects of exercise training are at least partly mediated through opioid receptor-dependent mechanisms in ischemia-reperfusion models. METHODS: Male Wistar rats (n = 76) were randomly assigned to 7 groups: (1) control; (2) exercise training; (3) morphine; (4) intermittent ischemia-reperfusion (three alternating periods of left anterior descending coronary occlusion and reperfusion); (5) exercise training+morphine; (6) naloxone (a non-selective opioid receptor blocker) plus morphine; (7) naloxone before each exercise-training session. Myocardial infarction was established in all groups by left anterior descending coronary ligation. Exercise training was performed on a treadmill for 60 minutes, 5 times/week, for 12 weeks, at 60% peak oxygen (peak VO2). Infarct size was histologically evaluated. RESULTS: Exercise training significantly increased exercise capacity and ΔVO2 (VO2 peak - VO2 rest) (p